2006
DOI: 10.1164/rccm.200510-1606oc
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of Peak Flow versus Symptom Monitoring in Older Adults with Asthma

Abstract: Objective: To determine whether peak flow monitoring has value above and beyond symptom monitoring when used as part of an asthma management plan. Methods: From a large managed-care organization, 296 adults, aged 50-92 yr, were recruited and randomly assigned in equal numbers to either use of symptoms or peak flow rate (twice daily or "as needed") for asthma monitoring, and monitored every 6 mo for 2 yr. Interventions were delivered in four 90-min small-group classes and included a personalized action plan and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 37 publications
0
36
0
4
Order By: Relevance
“…Clear modifications of peak expiratory flow are not necessarily associated with any alteration in FEV1, and exacerbations of asthma are observed without any change in peak expiratory flow [14]. Studies do not support the hypothesis that routine peak expiratory flow monitoring is better than monitoring of overall symptoms as an asthma self-management plan, either in adults or in children [3][4][5].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Clear modifications of peak expiratory flow are not necessarily associated with any alteration in FEV1, and exacerbations of asthma are observed without any change in peak expiratory flow [14]. Studies do not support the hypothesis that routine peak expiratory flow monitoring is better than monitoring of overall symptoms as an asthma self-management plan, either in adults or in children [3][4][5].…”
Section: Discussionmentioning
confidence: 96%
“…High healthcare use, including hospitalisation, is a characteristic of these patients [2]. The addition of home peak expiratory flow monitoring to a symptom-based self-management plan does not improve asthma outcome [3][4][5]. Preliminary studies have demonstrated the feasibility of using a spirometer or peak flow meter and recording data, which are transferred via telephone or internet to medical personnel.…”
mentioning
confidence: 99%
“…Beasley (9) was the first to teach patients how to adjust their ICS doses according to their peak expiratory flow (PEF) measurements. However, later studies in which PEF and symptom-based self-management programs have been compared have shown controversial results (10). Selfmanagement training programs introduced in specialist clinics have been shown to be effective in the short *Correspondence author: Jouni Hedman, M.D., Ph.D., Department of Pulmonary Diseases, South Karelia Central Hospital, Valto Käkelän katu 1, 53130 Lappeenranta, Finland; Fax: +358 5352 5895; E-mail: jouni.hedman@pp1.inet.fi term (11)(12)(13)(14), but the long-term results are inconsistent, depending on the primary outcomes (15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Cette mesure du DEP peut ê tre ré alisé e avec un dé bitmè tre classique ou avec un dé bitmè tre é lectronique [22]. Gautrin [24]. Le DEP reste toutefois un outil important dans la prise en charge de l'asthme puisqu'il permet de dé pister les patients qui ont une mauvaise perception de l'obstruction bronchique ou de la dyspné e, objectivé e chez 1 patient asthmatique sur 4 [25].…”
Section: Dé Bit Expiratoire De Pointeunclassified